Urban living alters moult dynamics in a passerine. (16th December 2015) - Hope, Sydney F.; Stabile, Frank A.; Butler, Luke K.
Abstract : Urbanization and habitat fragmentation can alter the timing of life history events, potentially leading to phenological mismatches, carryover effects, and fitness costs. Whereas urbanization and fragmentation are known to alter important aspects of breeding in many bird species, little is known about the effects of urbanization and habitat fragmentation on moult. To investigate the effects of urbanization and fragmentation on the annual moult, we compared the moult dynamics (onset, duration, and intensity) of urban, fragmented forest, and contiguous forest populations of the Carolina chickadee, a North American resident passerine that moults once per year immediately following the breeding season. Over three years, moult dynamics were similar in contiguous and fragmented forest populations, but wing moult started significantly earlier, and onset of moult varied less among years, in urban chickadees than in forest chickadees (fragmented and contiguous habitats pooled). Duration of wing moult did not differ between urban and forest populations, but urban birds moulted significantly fewer feathers simultaneously during peak moult, suggesting that individual feathers grew more rapidly. Our results show that urban living alters critical aspects of moult dynamics in a widespread songbird. Given the importance of moult dynamics for fitness during subsequent life history stages, and the large number of songbird species inhabiting urban areas, these results reveal previously unrecognized and potentially costly carryover effects of urban living on songbirds.